Establishment of an animal model of immune‐related adverse events induced by immune checkpoint inhibitors - Yuan Meng; Yingge Lv; Meng Shen; Wenwen Yu; Yumeng Liu; Ting Liu; Gen Liu; Shiya Ma; Zhenzhen Hui; Xiubao Ren; Liang Liu (Cancer Medicine)
Abstract Objective Immunotherapy, specifically immune checkpoint inhibitors (ICIs), has revolutionized cancer treatment. However, it can also cause immune‐related adverse events (irAEs). This study aimed to develop a clinically practical animal model of irAEs using BALB/c mice. Methods Subcutaneous tumors of mouse breast cancer 4T1 cells were generated in inbred BALB/c mice. The mice were treated with programmed death‐1 (PD‐1) and cytotoxic t‐lymphocyte antigen 4 (CTLA‐4) inhibitors once every 3 days for five consecutive administration cycles. Changes in tumor volume and body weight were recorded. Lung computed tomography (CT) scans were conducted. The liver, lungs, heart, and colon tissues of the mice were stained with hematoxylin–eosin (H&E) staining to observe inflammatory infiltration and were scored. Serum samples were collected, and enzyme‐linked immunosorbent assay (ELISA) was used to detect the levels of ferritin, glutamic‐pyruvic transaminase (ALT), tumor necrosis factor‐α (TNF‐α), interferon‐gamma (IFN‐γ), and interleukin‐6 (IL‐6). Mouse liver and lung cell suspensions were prepared, and changes in macrophages, T cells, myeloid‐derived suppressor cells (MDSCs), and regulatory (Treg) cells were detected by flow cytometry. Results Mice treated with PD‐1 and CTLA‐4 inhibitors showed significant reductions in tumor volume and body weight. The tissue inflammatory scores in the experimental group were significantly higher than those in the control group. Lung CT scans of mice in the experimental group showed obvious inflammatory spots. Serum levels of ferritin, IL‐6, TNF‐α, IFN‐γ, and ALT were significantly elevated in the experimental group. Flow cytometry analysis revealed a substantial increase in CD3+T cells, Treg cells, and macrophages in the liver and lung tissues of mice in the experimental group compared with the control group, and the change trend of MDSCs was opposite. Conclusions The irAE‐related animal model was successfully established in BALB/c mice using a combination of PD‐1 and CTLA‐4 inhibitors through multiple administrations with clinical translational value and practical. This model offers valuable insights into irAE mechanisms for further investigation.